2019
DOI: 10.1038/s12276-019-0279-2
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of chloride intracellular channel 1 enhances Ca2+ and reactive oxygen species signaling in A549 human lung cancer cells

Abstract: Chloride intracellular channel 1 (CLIC1) is a promising therapeutic target in cancer due to its intrinsic characteristics; it is overexpressed in specific tumor types and its localization changes from cytosolic to surface membrane depending on activities and cell cycle progression. Ca2+ and reactive oxygen species (ROS) are critical signaling molecules that modulate diverse cellular functions, including cell death. In this study, we investigated the function of CLIC1 in Ca2+ and ROS signaling in A549 human lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…This is likely because, in contrast to solid malignancies, aggressive leukemias like AML depend on cellular oxidative phosphorylation for proliferation which is supported by upregulation of respiratory complex genes(47). Various studies also suggest dysregulation of chloride ion channels such as the CLIC1 gene which plays a role in drug resistance and progression of various malignancies(22, 48). Although, the role of CLIC1 in AML is still unexplored, we observed significant upregulation of CLIC1 in paediatric AML with adverse prognostic impact.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because, in contrast to solid malignancies, aggressive leukemias like AML depend on cellular oxidative phosphorylation for proliferation which is supported by upregulation of respiratory complex genes(47). Various studies also suggest dysregulation of chloride ion channels such as the CLIC1 gene which plays a role in drug resistance and progression of various malignancies(22, 48). Although, the role of CLIC1 in AML is still unexplored, we observed significant upregulation of CLIC1 in paediatric AML with adverse prognostic impact.…”
Section: Discussionmentioning
confidence: 99%
“…Here, patients with CLIC1-positive tumors have demonstrated worse overall survival compared to those with CLIC1-negative tumors [ 35 ]. CLIC1 expression is correlated to a poor prognosis not only in pancreatic cancer, but also in tumors as lung cancer [ 36 ], ovarian cancer, where CLIC1 upregulation was correlated to chemotherapy resistance [ 37 ], gallbladder, and gastric cancers [ 38 ], where it was found to promote cells proliferation via MAPK/AKT regulation [ 39 ] and facilitates the formation of tumor-associated fibroblasts [ 40 ]. In addition, CLIC1 protein upregulation correlates with the level of aggressiveness and metastatic potential of colorectal cancer cells [ 41 ], where it was demonstrated to regulate cell volume and ROS level.…”
Section: Clic1 During Chronic Allostasismentioning
confidence: 99%
“…In addition, it has been found that high CLIC1 expression may inhibit the proliferation of GC cells and promote their apoptosis, migration and invasion [57,67]. It has been shown that CLIC1 acts as a sensor and effector during oxidative stress [70] and affects the progression of various tumors through ROS regulation [69][70][71][72][73]. Previous studies have also shown that hypoxia-reoxygenation (H-R) may increase intracellular ROS levels to activate the MAPK/ERK pathway and that the CLIC1 protein participates in the migration of LOVO colon cancer cells by regulating the ROS/ERK pathway during H-R [69].…”
Section: Clic1 Participates In the Metastasis And Invasion Of Gc Cells By Regulating Hypoxia-reoxygenationinduced Intracellular Rosmentioning
confidence: 99%